Incidence of Prediabetes and Type 2 Diabetes among People Aged over 20 Years in Ahvaz: A 5-Year Perspective Study (2009–2014) - Seyed Mahmoud Latifi; Majid Karandish; Hajieh Shahbazian; Leila Hardani Pasand (Journal of Diabetes Research)
Background. The present study is the fourth cohort study conducted in the Middle East on the evaluation of prediabetes and type 2 diabetes, implemented in Ahvaz, Iran. Methodology. The individuals aged over twenty years who had participated in a study on the prevalence of metabolic syndrome in 2009 (Phase 1) in Ahvaz were invited again in 2014. The questionnaires were completed via interview, and anthropometric parameters were measured by standard method. The logistic regression and chi-square test were used for data analysis. Results. In the median of five-year follow-up, a number of 593 people participated in reexamination from which 396 individuals were nondiabetic in Phase 1. The incidence of diabetes and prediabetes was 21.9 and 40.6 per 1000 person-years, respectively. Among Phase 1 prediabetics, 16.8% were diagnosed with diabetes in a five-year period. The factors affecting the incidence of prediabetes among the people younger than 65 years include age, family history of diabetes, and gender. The age factor plays an important role in the transformation of prediabetes to diabetes. Conclusion. The city of Ahvaz with type 2 diabetes incidence of 13.64 per 1000 person-years is one of the areas with high incidence of diabetes in Iran.